Can Neutrophil/Lymphocyte Ratio Assess Inflammatory Bowel Disease Activity and Severity in Children? - Metwally, Rasha Hassan (Turkish Journal of Gastroenterology, 2022)
Background: Laboratory markers such as white blood cells, C reactive protein, and erythrocyte sedimentation rate can aid in assessing the activity of inflammatory bowel disease but lacks sensitivity and specificity. Fecal calprotectin has higher sensitivity and specificity but it is expensive. Endoscopy is an invasive, inconvenient procedure having complications. No studies are done concerning the neutrophil/lymphocyte ratio in inflammatory bowel disease in pediatrics. The aim of this study was to assess the neutrophil/lymphocyte ratio as a laboratory marker of inflammatory bowel disease activity and severity in children. Methods: This is a prospective study. The study included all patients from 2 months up to 16 years who were confirmed to have inflammatory bowel disease endoscopically and histopathologically. Clinical activity score and Mayo endoscopic subscore were recorded. Laboratory investigations including white blood cells, C reactive protein, erythrocyte sedimentation rate, and fecal calprotectin were done on all patients. The neutrophil/lymphocyte ratio was calculated and correlated with different activity markers. Results: We included 50 inflammatory bowel disease patients. The mean neutrophil/lymphocyte ratio in ulcerative colitis was 1.76 ± 0.36, Crohn’s disease was 1.50 ± 0.41, and it was 1.47 ± 0.14 in indeterminate colitis. Neutrophil/lymphocyte ratio was significantly correlated to erythrocyte sedimentation rate, C reactive protein, fecal calprotectin, clinical activity score, and Mayo endoscopic subscore. Conclusion: Neutrophil/lymphocyte ratio can be used as an activity and severity marker in children with inflammatory bowel disease. Cite this article as: Metwally RH. Can neutrophil/lymphocyte ratio assess inflammatory bowel disease activity and severity in children?. Turk J Gastroenterol. 2022;33(12):1058-1061.